Cost-benefit analysis of milkish (Chanos chanos) farming at Kataisan Mariculture in San Jose, Tacloban City - Cruz, Maria Josefa D.; Siguan, Andrea Monique A.; Timkang, Fattie Heart Y.
For the past four years, Leyte has seen a decline in aquaculture production despite a pressing demand for aquatic food. This is concerning as the industry's peak productivity is crucial for meeting these demands. In light of this, the study aimed to conduct a cost-benefit analysis on the Milkfish (Chanos chanos) farming at Kataisan Mariculture in San Jose, Tacloban City to assess both its profitability and its production, with Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Internal Rate of Return (IRR) as criteria. The study obtained data from all fifteen (15) fish operators in the research area, revealing that most respondents were middle-aged men with undergraduate degrees. The results indicate a favorable net present value, a beneficial benefit-cost ratio above 1, and a 4% internal rate of return, demonstrating the profitability and success of fish farms. However, challenges such as limited access to stocking materials, fluctuating milkfish prices, adverse weather conditions, and the Tacloban Causeway project are hindering the full potential of fish farms.